Integral Operator Defined by k-th Hadamard Product - Maslina Darus; Rabha W. Ibrahim (Institute for Research and Community Services (LPPM) ITB, 2010)
We introduce an integral operator on the class A of analytic functions in the unit disk involving k Æ’ th Hadamard product (convolution) corresponding to the differential operator defined recently by Al-Shaqsi and Darus. New classes containing this operator are studied. Characterization and other properties of these classes are studied. Moreover, subordination and superordination results involving this operator are obtained.",